Effets de la marchandisation de l’arganier sur la vie socioéconomique des populations de l’arganeraie marocaine - Larbi Aziz; Marc Mormont; Khallil Allali (VertigO)
Tree in multi-use, the argan tree is also in multifunction : economic, social and environmental. He(it) was, and it is still, an important element of the local agrarian system and participates in the preservation of a particular biodiversity. As it always configured and gave rhythm to the life of the populations of the arganraie because it was (or one of its products) always present in their culinary, festive or sociocultural activities. However, the boom of the market of the argan engendered multiple consequences on the socioeconomic and cultural life of these populations. To understand and analyze these evolutions and the new local dynamics which take place there, we realized an empirical study in the region of Essaouira at the level of two rural districts. What allowed us, besides the historic analysis, to compare the dynamics which are in progress at the level of these two municipalities Our main results show that the craze for the products of the argan tree and the fit of their prices (in particular the oil) have re-configured the local socioeconomic and cultural life : new actors appeared, a market insufficiently structured and not rather profitable in premises was set up, the local know-how affects, new modes of food made their appearance, customs and traditions are endangered, etc.